ChemInform Abstract: Nickel and Cobalt‐Catalyzed Coupling of Alkyl Halides with Alkenes via Heck Reactions and Radical Conjugate Addition. Issue 39 (5th September 2013) - Qian, Qun; Zang, Zhenhua; Chen, Yang; Tong, Weiqi; Gong, Hegui
Abstract Review: 56 refs.